Higher plasma AFB1 concentration is associated with increased risk of HPV 16 and HPV 18 detection and persistence among Ugandan women - Yan Tong; Miriam Nakalembe; Collins Mpamani; Carolyn Nakisige; Jane Namugga; Grace Banturaki; Philiph Tonui; Omenge Orang’o; Kapten Muthoka; Anthony Ngeresa; John Groopman; Sean Burke; et al. (Environmental Health)
Abstract Introduction Aflatoxins are environmental hazards; potent carcinogenic and immunosuppressive agents that contaminates corn and other crops. A high proportion of hepatocellular carcinoma cases are caused by exposure to dietary aflatoxins. Cervical cancer is common among Ugandan women; this malignancy is caused by persistent infection with oncogenic HPV types. An analysis was performed to examine associations between plasma aflatoxin B1 (AFB1) detection and oncogenic HPV detection (HPV types 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68) and persistence among Ugandan women. Methods Ugandan women were enrolled in a prospective cohort study. Annual cervical swabs (Enrollment, Month 12 and Month 24) were tested for oncogenic HPV. Plasma AFB1 concentration was measured (as AFB1-lysine conjugate, or AFB1-lys) at Enrollment and Month 12. Multivariable regression models were fitted to examine associations of plasma AFB1-lys concentrations and oncogenic HPV controlling for demographic and behavioral characteristics. Results The analytical sample consisted of 114 women with a mean age of 33.2 years; 60 women were living with HIV; 59 were receiving antiretroviral therapy (ART) at enrollment. AFB1-lysine adducts (AFB1-lys) was detected in plasma from all 114 women. Multivariable regression models showed that plasma AFB1-lys concentration was associated with a higher risk of detection of HPV 16 (OR = 2.64, 95% CI = 1.42–4.90, p = 0.002) and HPV 18 (OR = 2.24, 95% CI = 1.27–3.96, p = 0.005), and persistence of HPV 16 (OR = 3.16, 95% CI = 1.59–6.26, p = 0.001) and HPV 18 (OR = 2.06, 95% CI = 1.09–3.90, p = 0.025), controlling for age, marital status, years of education, home ownership, distance to health care, number of lifetime sex partners, age of first sex, and HIV status. Conclusions AFB1 is an environmental hazard that is prevalent among Ugandan women. Higher plasma AFB1-lys concentration was associated with detection and persistence of HPV 16 and HPV 18; this association was independent of HIV status. As a result, these women may be at increased risk of cervical cancer. Further studies are needed to determine the mechanisms involved.